Wood Structure of Clethra monostachya Rehder and Wilson - Raturi, R. D.; Dayal, R. (Indian Forester, 1988)
Anatomical structure of the wood of Clethra monoslachya Rebder & Wilson of the family Cletbraceae has been described.